A nano-structured bilayer asymmetric wettability textile for efficient personal thermal and moisture management in high-temperature environments - Gu, Bin; Fan, Fan; Xu, Qihao; Shou, Dahua; Zhao, Dongliang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Banana tree waste is a promising renewable bio-resources.•A novel thermal-insulating aerogel membrane textile is proposed and fabricated.•The BAWCM integrates thermal insulation, evaporative cooling, and radiative cooling functions.•The BAWCM achieves personal thermal and moisture management in high temperature environments. In recent years, climate change has led to extremely hot weather conditions in many parts of the world, which not only causes large amount of energy consumption for building space cooling, but also poses a great threat to the health and safety of people outdoors. A wearable textile that could simultaneously maximizing thermal insulation, facilitating evaporative cooling, and enhancing radiative cooling would play an important role for outdoor personal thermal and moisture management in high-temperature environments. However, developing such a textile with a relatively simple structure remains a huge challenge. Herein, a bilayer asymmetric wettability cooling membrane (BAWCM) textile composed of banana trees cellulose aerogel membrane (BTCAM) and thermoplastic polyurethane nanofibers doped with zinc oxide nanoparticles (ZnO-NPs/TPU) is prepared by freeze-drying and subsequent electrospinning. The BAWCM textile has good thermal insulation performance, thereby reducing heat input when the ambient temperature is higher than the human body temperature. Meanwhile, the textile possesses a high reflectance of 91.3 % in the 0.37–2.5 μm wavelength range and an infrared emissivity of 90.2 % in the 8–13 μm wavelength range. In outdoor test, it is demonstrated that the BAWCM textile can be as large as 9.3 °C cooler than cotton under direct sunlight. More importantly, the textile can effectively achieve directional perspiration to accelerate evaporative cooling, preventing sticky and hot sensation. Through the integration of excellent thermal insulation, enhanced radiative cooling, and continuous sweat wicking-drying capability, this novel textile exhibits significantly improved personal thermal and moisture management performances in high-temperature environments.